A Rare Presentation of Orthostatic Tremor as Abdominal Tremor. (4th December 2018) - Mousele, Christina; Bentley, Paul; Tai, Yen F.
Background: Orthostatic tremor (OT) is a weight-bearing hyperkinetic disorder characterized by unsteadiness while standing that is relieved when sitting or walking. Case report: A 66-year-old male presented with a 5 year-history of tremor in his abdomen, but only when he stood in a stationary position. The tremor disappeared when he stood or walked. On examination, he had palpable tremor in his rectus abdominis and gastrocnemius virtually instantaneously after standing. His electromyography findings confirmed the presence of a 12-Hz tremor in the tibialis anterior while standing, with subharmonics recorded in the external obliques and rectus abdominis. Discussion: Our case illustrates an unusual presentation of OT. The diagnosis is supported by its characteristic frequency and specific appearance only during upright stance.